2014
DOI: 10.1038/ijo.2014.207
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the association between stop-signal reaction times, body mass indices and/or spontaneous food intake in pre-school children: an early model of compromised inhibitory control and obesity

Abstract: At 48 months of age, slower response inhibition on the Stop-Signal Task associates with higher BMI z-scores in girls, and with higher intake of carbohydrates and sugars during a snack test across both genders. Ongoing follow-up of these children will help clarify the implications of these associations for longer term macronutrient intake, eating-related pathology and/or pathological weight gain over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 25 publications
1
30
1
Order By: Relevance
“…the most appropriate test as per our a priori hypotheses), which can be used for future power calculations with higher doses and/or longer duration. The stop signal reaction time is a measure of inhibitory control, where a lower time indicates greater inhibitory control, which has been shown to be impaired with obesity [41]. This may indicate that with higher doses and/or more participants, liraglutide may increase inhibitory control, but this will need to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…the most appropriate test as per our a priori hypotheses), which can be used for future power calculations with higher doses and/or longer duration. The stop signal reaction time is a measure of inhibitory control, where a lower time indicates greater inhibitory control, which has been shown to be impaired with obesity [41]. This may indicate that with higher doses and/or more participants, liraglutide may increase inhibitory control, but this will need to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Decades of research by developmental scientists demonstrates that positive parent-child relationships support children’s development of self-regulation [18, 19]. There is evidence that children who have lower levels of self-regulation have increased risk for obesity [2026], but this is an emerging area of research [27], and what is meant by “self-regulation” in relation to children’s risk for obesity varies across studies.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the stop signal task or go/no-go task is often used to measure cognitive or inhibitory control [2-4] and can be combined with fMRI to study these complex mechanisms in the brain. Previous studies have found longer stop signal reaction times (SSRTs), which represent poorer inhibitory control, to correlate with future weight gain [5]. Intensive lifestyle changes decrease SSRTs, representing improved inhibitory control, in adolescents [6].…”
Section: Techniques To Study the Cns In Clinical Researchmentioning
confidence: 99%
“…The prefrontal cortex composes much of the cognitive control network, particularly the cingulate cortex, inferior frontal cortex, pre-supplementary motor area (pre-SMA) and dorsolateral prefrontal cortex (DLPFC) [184]. Several studies have demonstrated impaired inhibitory control in obese humans and a link of impaired control to future weight gain in normal weight individuals [4, 5, 179, 185-195]. Poorer inhibitory control, even on non-food-related tasks, has been observed to correlate with high calorie food intake [5] and a resistance to losing weight [195].…”
Section: Cognitive Control Systemsmentioning
confidence: 99%
See 1 more Smart Citation